STUDY REGARDING THE IDENTIFICATION OF THE PROMOTIONAL METHODS FOR ALBA IULIA CITY AS A TOURISTIC DESTINATION - Moisă, Claudia Olimpia; Lazea, Ruxandra (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
This scientific paper has as main objective the identification of the main promotional methods that can be used to promote Alba Iulia City as a touristic destination, more exactly of the touristic resources that are present in the locality with the purpose of attracting a large number of Romanian and foreign tourists with the help of traditional and on-line promotion methods. The present study will be focused mainly on the largest Vauban Citadel from East and South East Europe. In order to identify the promotional methods that are most suitable to promote the Alba Iulia City as a touristic destination a research will be conducted using a questionnaire.